Pemberdayaan KTH Jekoni dalam Pengembangan Agroforestri Kopi Robusta Sabet Berbasis Perhutanan Sosial Melalui Peningkatan Kualitas dan Pemasaran Digital: Pengabdian - Faizin, Rusdi; Wijaksena, Ego Ibnu; Fajri, Maulidil; Diman, Banta; Pramulya, Rahmat; Darmansyah, Dedy (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This community service program aims to improve production capacity, post-harvest quality, and robusta coffee marketing strategies at the Jekoni KTH in Sabet Village, Aceh Jaya. The main problems include substandard cultivation practices, inconsistent harvest quality, and marketing that still relies on collectors without product identification. Activities are carried out in a participatory manner through training in Good Agricultural Practices, natural post-harvest processing methods, hygienic storage, packaging design, and digital promotion. The results show a significant increase in farmer knowledge and skills, coffee quality with a red fruit harvest above 80%, a cupping score of 83.00, and the development of the "Green Coffee Sabet" product with ready-to-sell packaging and Instagram promotion. Overall, this activity increases the empowerment of partners to become independent and strengthens the competitiveness of local coffee through quality improvement and digital marketing.